Safety and tolerability of ranibizumab in uni/bilateral neovascular age-related macular degeneration: 12-month TWEYEs study. Issue 1 (11th May 2019) - Bandello, Francesco; Staurenghi, Giovanni; Ricci, Federico; Midena, Edoardo; Viola, Francesco; Lupieri Sinibaldi, Tommaso; Colombo, Laura; Peruzzi, Elena; Bassanini, Stefania
Abstract : Background: To evaluate the safety and tolerability of ranibizumab 0.5 mg in patients with uni/bilateral neovascular age-related macular degeneration (nAMD) and best-corrected visual acuity (BCVA)<2/10 and/or second eye affected, regardless of BCVA. Methods: In this 12-month, prospective, multicentre, open-label, single arm, pragmatic interventional study, patients (N=941) aged ≥ 50 years were to receive ranibizumab as per approved label, monthly until maximum stable visual acuity (VA) was achieved (initially, three or more injections may be required). Thereafter, patients were to be monitored monthly for VA and treatment was to be resumed if VA was reduced due to disease activity. Results: Of the 936 patients treated with ranibizumab at least once during the study, 823/113 were unilaterally/bilaterally (not simultaneously) treated . The mean (SD) number of ranibizumab injections during the study was 5.4 (2.9)/10.6 (5.0) injections in uni/bilaterally treated patients. Three systemic drug-related adverse events (AEs) (all serious, all in unilaterally treated patients) and 18 systemic AE of special interest (AESIs) (11 serious, 16/2 in unilaterally/bilaterally treated patients) occurred during the study. The annual incidence rate (AIR) (events/1000 person-years) for systemic drug-related AEs, considering a 15-day/30-day risk period, 11.0/8.5 for unilaterally treated patients. Considering the same risk period, the AIR (events/1000 person-years) for systemic AESIs for unilaterally treated patients was 22.1/19.9. Considering a 30-day risk period, the AIR (events/1000 treated eye-years) of ocular drug-related AEs was 23 and AESIs was 11.5. Conclusions: The low incidence of AEs and AESIs demonstrated the good safety and tolerability of ranibizumab in unilaterally/bilaterally treated patients with nAMD in this real-world setting.